2019
DOI: 10.3390/cancers11040585
|View full text |Cite
|
Sign up to set email alerts
|

Deletions of Chromosome 7q Affect Nuclear Organization and HLXB9Gene Expression in Hematological Disorders

Abstract: The radial spatial positioning of individual gene loci within interphase nuclei has been associated with up- and downregulation of their expression. In cancer, the genome organization may become disturbed due to chromosomal abnormalities, such as translocations or deletions, resulting in the repositioning of genes and alteration of gene expression with oncogenic consequences. In this study, we analyzed the nuclear repositioning of HLXB9 (also called MNX1), mapping at 7q36.3, in patients with hematological diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Concerning MNX1 gene, the results agree with previous studies showing that this gene is transcriptionally inactive in lymphocytes of healthy donors, but highly expressed in subjects with myeloid leukemia [ 18 ] and in cells derived from leukemic subjects, as shown here in the cell line K562 where the gene is transcriptionally active. Several studies have shown that MNX1 is active only during embryonic development, and that in adults with leukemia, it is ectopically expressed in association with a re-localization towards the inner part of the nucleus, triggering the expression of one of the two alleles as a consequence of a chromosomal rearrangement involving the chromosome 7 [ 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Concerning MNX1 gene, the results agree with previous studies showing that this gene is transcriptionally inactive in lymphocytes of healthy donors, but highly expressed in subjects with myeloid leukemia [ 18 ] and in cells derived from leukemic subjects, as shown here in the cell line K562 where the gene is transcriptionally active. Several studies have shown that MNX1 is active only during embryonic development, and that in adults with leukemia, it is ectopically expressed in association with a re-localization towards the inner part of the nucleus, triggering the expression of one of the two alleles as a consequence of a chromosomal rearrangement involving the chromosome 7 [ 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in a cell culture model of breast cancer, there were distinct genome spatial rearrangements associated with proliferation status to that of carcinogenesis (Meaburn and Misteli, 2008). Similarly, although we find that changes in copy number did not correlated with propensity to reposition ( Supplementary Table 6 ; (Meaburn et al, 2009; Leshner et al, 2016; Meaburn et al, 2016), we can not fully rule out that structural genomic alterations have not influenced the spatial position of any of the genes in the tissues analyzed since, in some cases, genomic instability can lead to spatial reorganization of the genome (Croft et al, 1999; Taslerova et al, 2003; Harewood et al, 2010; Federico et al, 2019). Regardless, importantly for a clinical test, we find that even in the background of genomic instability it is still possible to use gene positioning to distinguish normal tissue from cancer (Meaburn et al, 2009; Leshner et al, 2016; Meaburn et al, 2016) and to stratify cancers into clinically distinct subgroups, as demonstrated in this study.…”
Section: Discussionmentioning
confidence: 67%
“…This translocation repositioned the MNX1 gene more internally in the nucleus than the wild type allele. The ectopic activation and overexpression of MNX1 were also described in relation to other chromosomal rearrangements observed on cell lines GDM1 [ 103 ] and K562 [ 27 ], as well as deletions observed in patients with hematological disorders [ 97 ]. In this latter case, the activated MNX1 gene was related to the type of breakpoints in the deleted chromosome 7, namely when the deletion joined the region with the MNX1 allele to a chromosomal band with high GC-level, thus finding a transcriptionally active nuclear compartment [ 97 ] ( Figure 3 ).…”
Section: Chromosomal Rearrangements and Nuclear Gene Repositioning In Cancersmentioning
confidence: 99%
“…The nucleus on the right shows the case of gene activation by repositioning the 7q36 band in a transcriptionally active compartment (close to the GC-rich 7q22 band), as opposed to what is presented in the nucleus in the center, where the deletion involving the GC-poor 7q21 band keeps the 7q36 band in the same transcriptionally inactive compartment. Modified from [ 97 ].…”
Section: Figurementioning
confidence: 99%